Physico-chemical Parameters and Trace Metals for testing of underground drinking water at Jalalpur- A Review - Saras Prakash Dr. Saras Tiwari; Dr. Rajnish Kumar Singh (International journal of economic perspectives, 2022)
Samples of underground drinking water were collected from ten different India Marks-II handpumps of public places at Jalalpur block of Jaunpur district (U.P.). These samples were collected during pre monsoon period of year 2021, following standard methods of sampling. For the assessment of underground drinking water contamination status of the ten different sites, following water quality parameters and trace metals were analysed: pH, TDS, Turbidity, Total hardness, Total alkalinity, DO, COD, BOD, Chloride, Fluoride, Ca, Mg, Fe, Mn, Pb, Ni, Cd, Zn, Cr. The data was compared with the drinking water quality standards prescribed by W.H.O